2019
DOI: 10.1016/j.surfcoat.2018.04.040
|View full text |Cite|
|
Sign up to set email alerts
|

On the S/W stoichiometry and triboperformance of WSxC(H) coatings deposited by magnetron sputtering

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…Differences are probably due to the slightly inferior morphological appearance as well as the small compositional differences. Overall, the coatings revealed comparable wear resistance to those available for TMD-C films in the literature [14,15,34,35] A small reduction in the CoF was verified for the MoSe and low carbon content coatings (MoSeC24 and MoSeC33). However, for the films with increased carbon content, the friction reduction was even higher.…”
Section: Tribological Propertiessupporting
confidence: 61%
See 1 more Smart Citation
“…Differences are probably due to the slightly inferior morphological appearance as well as the small compositional differences. Overall, the coatings revealed comparable wear resistance to those available for TMD-C films in the literature [14,15,34,35] A small reduction in the CoF was verified for the MoSe and low carbon content coatings (MoSeC24 and MoSeC33). However, for the films with increased carbon content, the friction reduction was even higher.…”
Section: Tribological Propertiessupporting
confidence: 61%
“…Differences are probably due to the slightly inferior morphological appearance as well as the small compositional differences. Overall, the coatings revealed comparable wear resistance to those available for TMD-C films in the literature [ 14 , 15 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 62%
“…On the other hand, amorphous carbon coatings provide high hardness but are not suitable for applications that work in dry atmospheres. Therefore, a combination of carbon and TMDs was explored by various authors [18,[29][30][31][32][33][34][35][36], with the main idea to harvest the best properties of both materials and prepare the ultimate solid lubricant that will be able to reduce friction in diverse environments.…”
Section: Introductionmentioning
confidence: 99%
“…The films deposited by these different routes were studied in a time span of several years, and it is still not clear which is the best route for potential upscaling. A recent study performed on W-S-C(H) coatings [13] has shown that co-sputtered hydrogen-free coatings display the best tribological performance, with evidence that the C phase plays a role in the frictional response during sliding in ambient air conditions, contrary to the studies done by Polcar and Cavaleiro. A major issue regarding the synthesis of TMD-containing thin films by way of magnetron sputtering is the sub-stoichiometry in relation to the S/M ratio (M-transition metal, S-chalcogen atom), which is often much lower than the stoichiometric value of 2. The sub-stoichiometry has a strong effect on the tribological properties and the hardness of the films.…”
Section: Introductionmentioning
confidence: 77%